Reactive oxygen species, inflammation and calcium oxalate nephrolithiasis - Khan, Saeed R. (Translational Andrology and Urology, 2014)
Calcium oxalate (CaOx) kidney stones are formed attached to Randall’s plaques (RPs) or Randall’s plugs. Mechanisms involved in the formation and growth are poorly understood. It is our hypothesis that stone formation is a form of pathological biomineralization or ectopic calcification. Pathological calcification and plaque formation in the body is triggered by reactive oxygen species (ROS) and the development of oxidative stress (OS). This review explores clinical and experimental data in support of ROS involvement in the formation of CaOx kidney stones. Under normal conditions the production of ROS is tightly controlled, increasing when and where needed. Results of clinical and experimental studies show that renal epithelial exposure to high oxalate and crystals of CaOx/calcium phosphate (CaP) generates excess ROS, causing injury and inflammation. Major markers of OS and inflammation are detectable in urine of stone patients as well as rats with experimentally induced CaOx nephrolithiasis. Antioxidant treatments reduce crystal and oxalate induced injury in tissue culture and animal models. Significantly lower serum levels of antioxidants, alphacarotene, beta-carotene and beta-cryptoxanthine have been found in individuals with a history of kidney stones. A diet rich in antioxidants has been shown to reduce stone episodes. ROS regulate crystal formation, growth and retention through the timely production of crystallization modulators. In the presence of abnormal calcium, citrate, oxalate, and/or phosphate, however, there is an overproduction of ROS and a decrease in the antioxidant capacity resulting in OS, renal injury and inflammation. Cellular degradation products in the urine promote crystallization in the tubular lumen at a faster rate thus blocking the tubule and plugging the tubular openings at the papillary tips forming Randall’s plugs. Renal epithelial cells lining the loops of Henle/collecting ducts may become osteogenic, producing membrane vesicles at the basal side. In addition endothelial cells lining the blood vessels may also become osteogenic producing membrane vesicles. Calcification of the vesicles gives rise to RPs. The growth of the RP’s is sustained by mineralization of collagen laid down as result of inflammation and fibrosis.